Cuidado de las necesidades espirituales desde la perspectiva del paciente con enfermedad terminal Hospital Regional Docente de Trujillo 2010 - Arce Escobar, Lisbeth (2010)
This descriptive qualitative study, performed in the Trujillo Regional Teaching Hospital in the Medical Services A, B and C, during the month of February 2010, which is carried out to describe and understand the care of spiritual needs from the perspective of the patient with terminal illness. For data collection 8 subjects were considered participants to reach the saturation of the speeches. According to the results of that investigation, to make the conceptual approach, the patient with terminal disease states that during the care, the nursing staff passes on different feelings and attitudes, which were grouped into three categories: Spirituality in the Practice of Nursing Care resonances and dissonances Care. Found in these categories several sub categories, the most outstanding love, kindness, hope and faith. However, the patient experiencing a terminal illness goes through moments of pain and suffering both physically and spiritually and it is now that needs to be comforted through nursing care, which should include spaces for communication, forgiveness, hope and confidence the patient.